A study on commercial bank asset portfolio behavior: period of controls and liberalization (1975-1993) - Rabuyo, Grace Bello (Animo Repository, 1994)
The study determines the effect of policy returns in interest rate and exchange rate in the asset portfolio behavior of commercial banks during the period of financial controls and liberalization from 1975 to 1993. The asset portfolio behavior of commercial banks is the process by which the banks allocate their investible funds among alternative income producing assets. The study utilized the Micro Time-Series Package (TSP) 6 which used ordinary least square estimation. The equations for demands for loan portfolio, investment in treasury bills, investment in commercial papers and bank reserve position of commercial banks were estimated individually in log form so that the coefficients of the empirical results are presented in elasticities. The data for the study were obtained mainly from published reports and data from the Central Bank Statistics Office. The micro-economic theory tested in the study was the theory of portfolio choice. The portfolio diversification was based on the risk-return combination of risky and safe assets. The presentation of the conclusion is focused on the earnings or return only. The portfolio behavior of commercial banks during the period of financial control, as evidenced by the domestic credit elasticity of demands for loan, investment in treasury bills, and commercial paper, revealed that the commercial banking industry put their financial resources in portfolios that has higher variability in returns such as treasury bills and commercial papers than loan which was restricted by the administrative ceiling on loans. Furthermore, during the period of financial control, the sub-period regression for loan portfolio behavior revealed that the treasury bill interest rate elasticity of the demand for loan showed that it is inelastic (-0.037). This implied that increases in the treasury bill interest rate did not shift the financial resources from loans to treasury bills. The interest differential between the loan interest rate, although subject to administrative ceiling, and treasury bill interest rate was positive in favor of loan interest rate from 1975-1982.The portfolio behavior of commercial banks during the period of liberalization, as evidenced by the domestic credit elasticity of the demands for loan (1.0822), investment in treasury bills (0.8558) and investment in commercial papers (o.5747), revealed that banks put their financial resources in portfolios (loan) with higher returns. A review of the interest rate between loan and treasury bills showed that the loan interest rate was higher than the treasury bill from 1983 to 1993 except in 1984 and 1989.Furthermore, in the sub-period regression results for loan portfolio behavior during the period of financial liberalization, the treasury bill interest rate elasticity of the demand for loan revealed that it is inelastic -0.0879). This implied that increases in the treasury bill interest rate did not shift the financial resources loans to treasury bills. This corroborated the behavior of banks to favor investment in assets with higher returns. In summary, commercial banks invest their financial resources in assets with higher return or higher variability in returns.